Destabilization of crude oil emulsions via microwave assisted ultrasonic technology - Khairul Azirul, Muhamad Asrai (2013)
The conventional method of breaking emulsions using heat and chemicals are disadvantages from both economic and environmental aspects. Hence, the alternative method and environmental friendly are needed to alter efficiency for destabilization of crude oil emulsion. One of the alternatives that can be used to replace the existance chemical which is not enviromental friendly is by using microwave assisted ultrasonic technologies which create very high energy to break the presence of water in the crude oil. In this study, microwave assisted ultrasonic demulsification was applied in a 20-80 % and 50-50 % water-in-oil emulsions. The effectiveness of microwave assisted ultrasonic in demulsification was assessed experimentally with two different power of microwave which are 450 Watt and 600 Watt, and two different power of ultrasonic which are 3 and 9. A commercial emulsifiers used were Triton X-100, Low Sulphur Wax Residue (LSWR) and Span 83. The separation of water from crude oil is faster and efficient via using the microwave assisted by ultrasonic method compare to conventional method.